CCDC92 deficiency ameliorates podocyte lipotoxicity in diabetic kidney disease - Zuo, Fuwen; Wang, Youzhao; Xu, Xinlei; Ding, Ruihao; Tang, Wei; Sun, Yu; Wang, Xiaojie; Zhang, Yan; Wu, Jichao; Xie, Yusheng; Liu, Min; Wang, Ziying; et al. (Metabolism, clinical and experimental, 2024)
Podocyte injury is considered as the most important early event contributing to diabetic kidney disease (DKD). Recent findings provide new insights into the roles of lipids and lipid-modulating proteins as key determinants of podocyte function in health and kidney disease. CCDC92, a novel member of coiled-coil domain-containing protein family, was indicated relevant to lipid metabolism, coronary heart disease and type 2 diabetes. However, the expression pattern and role of CCDC92 in the kidney is not clear. This study was designed to elucidate the contribution of CCDC92 in the pathogenesis of DKD. Sections with a pathological diagnosis of different classes of DKD, including subjects with mild DKD (class II, n = 6), subjects with moderate DKD (class III, n = 6) or subjects with severe DKD (class IV, n = 6), and control samples (n = 12) were detected for the expression level of CCDC92 and lipid accumulation. Two types of diabetic mice model (db/db and HFD/STZ) in podocyte-specific Ccdc92 knockout background were generated to clarify the role of CCDC92 in podocyte lipotoxicity. The level of CCDC92 was increased in renal biopsies sections from patients with DKD, which was correlated with eGFR and lipid accumulation in glomeruli. In animal studies, CCDC92 were also induced in the kidney from two independent diabetic models, especially in podocytes. Podocyte-specific deletion of Ccdc92 ameliorated podocyte injury and ectopic lipid deposition under diabetic condition. Mechanically, CCDC92 promoted podocyte lipotoxicity, at least in part through ABCA1 signaling-mediated lipid homeostasis. Our studies demonstrates that CCDC92 acts as a novel regulator of lipid homeostasis to promote podocyte injury in DKD, suggesting that CCDC92 might be a potential biomarker of podocyte injury in DKD, and targeting CCDC92 may be an effective innovative therapeutic strategy for patients with DKD. [Display omitted] •CCDC92 is increased in podocytes under diabetic condition.•The level of CCDC92 in glomeruli is correlated with eGFR and lipid accumulation.•Conditional knockout of Ccdc92 in podocytes ameliorates glomerular injury.•CCDC92 contributes to podocyte lipotoxicity in DKD through regulation of ABCA1.